Respirer comme des chauves-souris - Michèle Cros (Anthropologie & Santé)
In Covid-19 times, respiratory problems have taken center stage : from the mandatory mask wearing in many public places to patients on ventilators in intensive care units, not to mention the “I can’t breathe” linked in particular to the Black Lives Matter movement. Due to their resting position bats breathe upside down. They therefore already know—even before they find themselves in a position of a defendant—about the respiratory ailments that lead humans, in a state of planetary suffocation, to imitate them involuntarily. A set of drawings from the Lobi country of Burkina Faso, collected in the post-Ebola period, illustrates this existential problem that transgresses all the boundaries of life.